Flammability properties of polymers and polymer composites combined with ionic liquids - Shamsuri, Ahmad Adlie; Mohamed Yusoff, Mohd Zuhri; Abdan, Khalina; Md. Jamil, Siti Nurul Ain (De Gruyter, 2023)
The flammability properties of polymers and polymer composites are crucial in ensuring their safe use in various applications. The development of flame-retardant technologies continues to be an active area of research to improve the fire safety of these materials. Recently, ionic liquids have been studied in the flammability properties of polymers and polymer composites. In this concise review, different types of polymers and polymer composites that are combined with ionic liquids are discovered. In addition, the preparation of polymers and polymer composites combined with ionic liquids through distinct methods is described. The additive effect of ionic liquids on the flammability properties of polymers and polymer composites is also concisely reviewed. The data demonstrated in this review contribute an extra visible knowledge of the preparation of polymers and polymer composites combined with ionic liquids and their flammability properties. In summary, certain types of ionic liquids can decrease the flammability properties of polymers and increase the flame retardancy of polymer composites.